Diaphragm and preparation method thereof and battery

By using electrospinning technology on the lithium battery separator, the composite fiber coating of bacidin or bacidin metal chelate and hydroxyl-containing polymer and other materials, the existing separator process is solved, and the excellent cycle performance and service life of lithium batteries are achieved under high temperature conditions.

CN119419445BActive Publication Date: 2025-04-04JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510026574.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-04
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The existing lithium battery separator modification process is complex and costly, making it difficult to apply on a large scale, and the battery cycle performance becomes worse under high temperature conditions.

Method used

A separator structure including a base film and a coating is adopted, wherein the coating is formed by a material such as bacidin or bacidin metal chelate and a hydroxyl-containing polymer through electrospin technology to form a uniform and dense composite fiber coating.

Benefits of technology

It achieves improved high-temperature cycling performance of the diaphragm and extended battery life, while reducing process complexity and cost, making it suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419445B_ABST
    Figure CN119419445B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of battery technology, and in particular to a diaphragm, a preparation method thereof, and a battery. The diaphragm comprises: a base film; a coating, which is arranged on at least one side surface of the base film along the thickness direction, and the coating comprises composite fibers; the composite fibers comprise a compound obtained by dehydration condensation of reactants A and reactants B; wherein the reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer, or an amine-containing polymer. wherein reactants A and B are stably bonded by covalent bonds, and a uniform and dense coating is formed on the interface of the base film by electrospinning. The diaphragm has excellent softness, high tensile strength, good hydrophilicity and sustained release properties, and also has the characteristics of stability, heat resistance, and excellent ionic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a diaphragm and a preparation method thereof, and a battery. Background Art

[0002] The main function of the battery separator is to physically isolate the positive and negative electrodes and prevent the electrons in the battery from passing through. At the same time, it can allow ions to pass through, so that lithium ions can be quickly transmitted when the positive and negative electrodes are embedded and unembedded, thereby completing the electrochemical charge and discharge process. Therefore, the separator has a vital impact on the performance of lithium batteries. Lithium battery separators are generally made of polyethylene (PE) or polypropylene (PP). During the charge and discharge process, due to the characteristics of the electrode material itself, metallic lithium dendrites are easily generated on the electrode surface. The growth of these dendrites will pierce the separator, causing the battery to short-circuit and fail, and even explode fuel and other dangers. Therefore, the battery separator is the key to battery safety. Therefore, a separator with excellent performance can directly affect the battery's cycle performance, internal resistance, and safety characteristics.

[0003] In recent years, lithium battery separator coating technology has developed rapidly. The existing technology prepares different gel polymer materials by initiating polymerization reactions and applies them to separator materials. Among them, some existing technologies prepare expensive gel polymer materials under complex process conditions such as high temperature conditions, ultraviolet light conditions, and high-concentration lithium salt initiators, but they cannot be applied on a large scale due to process or cost reasons. Therefore, a simple method is urgently needed to modify the separator to produce high-performance lithium-ion batteries with excellent cycle life. Summary of the invention

[0004] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a diaphragm and a preparation method thereof and a battery, which can modify the diaphragm in a simple manner, can solve the problems of complex process and high cost in the existing diaphragm modification process, and can also improve the high temperature cycle performance of the battery and increase the service life of the battery. In order to solve the above technical problems, the present application is implemented as follows:

[0005] According to one aspect of the present application, an embodiment of the present application provides a diaphragm, the diaphragm comprising:

[0006] Basement membrane;

[0007] A coating layer is disposed on at least one side surface of the base film along the thickness direction, and the coating layer includes composite fibers;

[0008] The composite fiber includes a compound obtained by dehydration condensation of reactant A and reactant B;

[0009] Wherein, the reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer.

[0010] In addition, the diaphragm according to the present application may also have the following additional technical features:

[0011] In some embodiments, the mass ratio of the reactant A to the reactant B is (20-25): (1-3).

[0012] In some embodiments thereof, the bacitracin metal chelate comprises at least one of bacitracin zinc, bacitracin copper, bacitracin manganese or bacitracin nickel.

[0013] In some embodiments, the reactant B includes at least one of polyethylene glycol, polylactic acid, polyamide, cellulose acetate or polyvinyl alcohol.

[0014] In some embodiments, the coating has a thickness of 10 μm to 35 μm.

[0015] In some embodiments, the base film has a thickness of 10 μm to 20 μm.

[0016] In some embodiments, the thickness ratio of the coating layer to the base film is 0.5 to 3.5.

[0017] In some of the embodiments, the base film includes at least one of a polypropylene film or a polyethylene film.

[0018] In some embodiments, the tensile strength of the diaphragm is 1.139 MPa ~ 2.186 MPa.

[0019] In some embodiments, the elongation at break of the diaphragm is 14.6% to 45.1%.

[0020] In some embodiments, the contact angle of the diaphragm is 16.274°~26.458°.

[0021] According to another aspect of the present application, an embodiment of the present application provides a method for preparing a diaphragm, comprising the following steps:

[0022] Adding reactant A to the solution and mixing to obtain a spinning solution, wherein the solution includes reactant B;

[0023] The spinning solution forms a coating on the base membrane by electrostatic spinning to obtain a diaphragm;

[0024] Wherein, the spinning solution contains a compound obtained by dehydration condensation of reactant A and reactant B;

[0025] The reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer.

[0026] In some embodiments, in the electrospinning step, the inner diameter of the spinneret is 0.5-0.7 mm.

[0027] In some of the embodiments, in the electrospinning step, the distance between the spinneret and the drum is 8 to 15 cm.

[0028] In some embodiments, in the electrospinning step, the spinning flow rate is 0.6-0.8 mL / h.

[0029] In some of the embodiments, in the electrospinning step, the positive high voltage at the spinneret of the electrospinning equipment is 15~25KV, and the negative high voltage at the drum is -3.5~-2.5KV.

[0030] In some of the embodiments, the solution is an aqueous solution comprising an acid.

[0031] In some embodiments, the mass fraction of the acid in the solution is 55% to 65%.

[0032] In some embodiments, the acid includes at least one of formic acid, acetic acid, hydrochloric acid or sulfuric acid.

[0033] In some embodiments, based on the mass of the solution, the mass fraction of the reactant B is 1% to 3%.

[0034] In some embodiments, based on the mass of the solution, the mass fraction of the reactant A is 20% to 25%.

[0035] In some embodiments, the method for preparing the Bacitracin metal chelate comprises:

[0036] The bacitracin is dissolved in a solvent and then mixed with a metal salt, and then dialyzed, centrifuged and dried to obtain a bacitracin metal chelate.

[0037] In some embodiments, the mass volume ratio of the bacitracin, the metal salt and the solvent is (5-30 mg): (15-90 mg): (50-100 mL).

[0038] In some embodiments, the solvent includes at least one of water, ethanol, methanol or dimethyl sulfoxide.

[0039] In some embodiments, the metal salt includes at least one of a metal hydrochloride or a metal sulfate, and the metal in the metal salt includes at least one of zinc, copper, manganese or nickel.

[0040] In some embodiments, in the dialysis step, the specification of the dialysis bag is 800~1200D, the water change interval is 3~5h, and the dialysis time is 22~26h.

[0041] In some embodiments, in the centrifugation step, the centrifugal speed is 8000-10000 rpm and the centrifugation time is 4-6 min.

[0042] In some embodiments, in the drying step, the drying temperature is 40-50°C.

[0043] According to another aspect of the present application, an embodiment of the present application provides a battery, including a diaphragm, wherein the diaphragm is the aforementioned diaphragm or a diaphragm prepared by the aforementioned preparation method.

[0044] Implementing the technical solution of the present invention has at least the following beneficial effects:

[0045] The diaphragm of the present application comprises reactant A (bacitracin or bacitracin metal chelate) and reactant B (hydroxyl-containing polymer, carboxyl-containing polymer, amide-containing polymer or amine-containing polymer). While using bacitracin or bacitracin metal chelate to contribute excellent fiber structure to the diaphragm coating, the polar functional groups on the short chain of bacitracin or bacitracin metal chelate can also be used to attract lithium ions migrating in the electrolyte, so as to better realize the transport of lithium ions; bacitracin metal chelate can improve the overall conductivity of the diaphragm, further optimize the lithium ion transport capacity of bacitracin, and produce synergistic effects with the polar functional groups on bacitracin to improve the transfer efficiency of lithium ions. The use of hydroxyl-containing polymers, carboxyl-containing polymers, amide-containing polymers or amine-containing polymers can solve the problem that bacitracin or bacitracin metal chelate is difficult to form a uniform coating on the base film, and the mechanical properties and wettability of the diaphragm can be further enhanced. Therefore, the diaphragm has excellent softness, high tensile strength, good hydrophilicity and sustained release properties, and also has the characteristics of stability, heat resistance and excellent ionic conductivity.

[0046] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 Shown is the SEM image of bacitracin zinc provided in Example 1 of the present invention.

[0048] Figure 2 Shown is a SEM image of bacitracin zinc in the surface coating of the composite diaphragm provided in Example 1 of the present invention after the composite diaphragm provided in Example 1 of the present invention is assembled into a battery and cycled 100 times.

[0049] Figure 3 Shown is a surface SEM image of the spinning coating provided in Example 1 of the present invention.

[0050] Figure 4 Shown are EIS graphs of Li-Cu half-cells during cycling of Comparative Example 1 and Example 1 of the present invention. DETAILED DESCRIPTION

[0051] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0052] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0056] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0057] In the related art, some separators include a base membrane and a coating disposed on the base membrane, which improves the high temperature resistance and cycle stability of the battery through the coating. However, the existing coating materials cannot be used on a large scale due to process or cost issues.

[0058] In view of this, an embodiment of the present application provides a diaphragm, the diaphragm comprising:

[0059] Basement membrane;

[0060] A coating layer is disposed on at least one side surface of the base film along the thickness direction, and the coating layer includes composite fibers;

[0061] The composite fiber includes a compound obtained by dehydration condensation of reactant A and reactant B;

[0062] The reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer.

[0063] The above-mentioned "the coating is disposed on at least one side surface of the base film along the thickness direction" means that the coating can be disposed on one surface of the base film along its own thickness direction, or on two surfaces of the base film along its own thickness direction. The "surface" here can be the entire area of ​​the base film, or a partial area of ​​the base film. For example, in this embodiment, the surface can be the entire area of ​​the base film. This application has no particular limitation on this, as long as the purpose of this application can be achieved.

[0064] As an example, the base film has two surfaces opposite to each other in its own thickness direction, and the coating layer is provided on the two opposite surfaces of the base film.

[0065] Particularly, in the diaphragm of the embodiment of the present application, the coating includes composite fibers; the composite fibers include a compound obtained by dehydration condensation of reactants A and B; after reactants A and B are mixed, they can be stably bonded in the form of covalent bonds, and are arranged at the interface of the base film to form a uniform and dense coating. In addition, the introduction of reactant B (polymer) also solves the problem that reactant A (bacitracin or bacitracin metal chelate) is difficult to form a uniform coating on the base film. At the same time, the coating can stably exist under hot, acidic and alkaline environmental conditions, and also has good mechanical properties and wettability.

[0066] Specifically, reactant A includes bacitracin or bacitracin metal chelate. In particular, bacitracin can contribute excellent fiber structure to the coating. It also has abundant polar groups (-NH2, -COOH or -CONH-, etc.). There are multiple chemical bonds and interactions between groups inside the bacitracin molecule. The hydrogen bonds and hydrophobic interactions within the molecule help maintain the stability of the molecule, which makes the composite fiber have excellent softness, high tensile strength, good hydrophilicity and sustained release properties, and enhances its compatibility with the basement membrane. In addition, the short chain of bacitracin has abundant polar functional groups, which can attract lithium ions migrating in the electrolyte and has strong lithium ion transport ability.

[0067] Bacitracin metal chelates introduce metals into the polypeptide system of bacitracin, which can optimize the metal transport capacity of bacitracin and produce synergistic effects with the polar functional groups on bacitracin to further increase the transfer rate of lithium ions. As a result, the conductivity efficiency of the diaphragm for lithium ions can be improved, which helps to achieve a smoother embedding and release process of lithium ions between the positive and negative electrodes, accelerate the charge transfer rate at the interface, and inhibit the growth of lithium dendrites, thereby extending the overall service life of the lithium battery. At the same time, bacitracin metal chelates also have all the advantages of the above-mentioned bacitracin.

[0068] In addition, reactant B includes at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer. The selected polymers have good mechanical properties, wettability, and spinning properties. They can stably exist in the electrolyte and enhance the mechanical and wettability of the diaphragm. They can also solve the problem that reactant A (bacitracin or bacitracin metal chelate) is difficult to form a uniform coating on the base membrane.

[0069] Based on this, the diaphragm of the present application comprises reactant A (bacitracin or bacitracin metal chelate) and reactant B (hydroxyl-containing polymer, carboxyl-containing polymer, amide-containing polymer or amine-containing polymer). While using bacitracin or bacitracin metal chelate to contribute excellent fiber structure to the diaphragm coating, the polar functional groups on the short chain of bacitracin or bacitracin metal chelate can also be used to attract lithium ions migrating in the electrolyte, so as to better realize the transport of lithium ions; bacitracin metal chelate can improve the overall conductivity of the diaphragm, further optimize the lithium ion transport ability of bacitracin, and produce synergistic effects with the polar functional groups on bacitracin to improve the transfer efficiency of lithium ions. The use of hydroxyl-containing polymers, carboxyl-containing polymers, amide-containing polymers or amine-containing polymers can solve the problem that bacitracin or bacitracin metal chelate is difficult to form a uniform coating on the base film, and the mechanical properties and wettability of the diaphragm can be further enhanced. Therefore, the diaphragm has excellent softness, high tensile strength, good hydrophilicity and sustained release properties, and also has the characteristics of stability, heat resistance and excellent ionic conductivity.

[0070] It should be noted that the present application does not limit the types of hydroxyl-containing polymers, carboxyl-containing polymers, amide-containing polymers, amine-containing polymers and bacitracin metal chelates, as long as they can be used to prepare the coating. Optionally, the hydroxyl-containing polymers, carboxyl-containing polymers, amide-containing polymers, amine-containing polymers and bacitracin metal chelates in the present application can be selected from the specific types listed below.

[0071] In some embodiments, the mass ratio of reactant A and reactant B is (20~25): (1~3). As an example, the mass ratio of reactant A and reactant B can be 20:1, 21:1, 20:2, 22:2, 23:1, 23:3, 24:1, 25:1, 25:3, etc., and of course it can also be other values ​​within the above range, which are not limited here. When the mass ratio of reactant A and reactant B is lower than 20:3, it will lead to incomplete reaction, which not only wastes raw materials, but also affects the purity of the product. When the mass ratio of reactant A and reactant B is higher than 25:1, each B will connect multiple A molecules, or the distribution of A on the B material chain will be too dense. This may change the spatial structure of the product, cause aggregation, and affect the stability of the product.

[0072] In some embodiments, the bacitracin metal chelate includes at least one of bacitracin zinc, bacitracin copper, bacitracin manganese or bacitracin nickel; preferably, the bacitracin metal chelate is bacitracin zinc, and when bacitracin reacts with metal ion zinc, a bacitracin zinc chelate (BACZ) with nanoscale micropores for ion migration can be generated, and the micropore size is 180nm-220nm. When it is applied to lithium-ion batteries, a large number of polar groups can attract lithium ions, and the micropores on its surface can be used as microchannels for lithium ion migration, promoting the insertion and removal of lithium ions. In addition, the microporous structure can also exist stably after multiple battery cycles during the battery cycle process. When the working environment temperature of the lithium-ion battery is high, there will be a situation where the chemical activity inside the battery is intensified and the migration rate of lithium ions is accelerated. Since bacitracin zinc itself has a microporous structure, it can effectively solve the problem of poor battery cycle performance when lithium ions are working in a high temperature working environment. Microchannels can guide lithium ions to be uniformly inserted and removed, further inhibiting the growth of lithium dendrites. At the same time, Bacitracin Zinc also has all the characteristics of the above-mentioned Bacitracin and Bacitracin metal chelate.

[0073] In some embodiments, reactant B includes, but is not limited to, at least one of polyethylene glycol, polylactic acid, polyamide, cellulose acetate, or polyvinyl alcohol. Preferably, reactant B is polyethylene glycol. The hydroxyl-containing polymer polyethylene glycol has excellent mechanical properties and moisture retention, which can further improve the tensile strength and hydrophilicity of the entire diaphragm; and polyethylene glycol also has strong thermal stability, and will not start to react with oxygen in the air until the temperature reaches above 120°C. Therefore, polyethylene glycol can significantly enhance the high temperature resistance of commonly used base film materials such as polypropylene (PP) or polyethylene (PE).

[0074] Preferably, reactant A is bacitracin zinc (BACZ) and reactant B is polyethylene glycol (PEG). If BACZ is simply coated on the base membrane, it is difficult to form a uniform and dense coating on the base membrane interface. For example, if BACZ is coated on the base membrane by electrospinning, it is difficult to form fibers with uniform diameter if pure BACZ is used for electrospinning. However, by using PEG and BACZ solutions as raw materials, a PEG / BACZ nanofiber layer with uniform diameter was prepared on the diaphragm using an electrospinning machine. The two polymers are mainly stably bound by forming covalent bonds through the carboxyl group (-COOH) on BACZ and the hydroxyl group (-OH) on PEG. The introduction of PEG makes the composite nanofibers have good mechanical properties and moisture retention. In addition, both PEG and BACZ have good heat resistance, which can improve the thermal stability of the diaphragm under high temperature conditions. At the same time, Zn on BACZ 2+ The introduction of enhances the ionic conductivity of PEG / BACZ nanofibers, and the polar groups and microchannels on BACZ can attract lithium ions and pass through them quickly, improving the performance of lithium-ion batteries under high temperature conditions.

[0075] In some embodiments, the thickness of the coating is 10 μm to 35 μm. As an example, the thickness of the coating can be 10 μm, 11 μm, 13 μm, 15 μm, 18 μm, 20 μm, 25 μm, 30 μm, 35 μm, etc., and of course it can be other values ​​within the above range, which is not limited here.

[0076] In some embodiments, the thickness of the base film is 10 μm to 20 μm. As an example, the thickness of the base film can be 10 μm, 11 μm, 13 μm, 15 μm, 16 μm, 17 μm, 18 μm, 20 μm, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0077] In some embodiments, the thickness ratio of the coating layer to the base film is 0.5 to 3.5. As an example, the thickness ratio of the coating layer to the base film is 0.5, 0.8, 1, 1.5, 1.6, 2, 2.3, 2.8, 3, 3.2, 3.5, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0078] By limiting the thickness and thickness ratio of the base film and the coating within the above range, the safety and reliability of the battery can be improved while ensuring the performance of the battery. Specifically, if the coating thickness ratio is too low, the improvement of the heat resistance of the separator is limited, and the thermal stability and ionic conductivity of the battery are difficult to be further guaranteed and optimized, and it is difficult to improve the service life of the battery; if the coating thickness ratio is too high, the transmission efficiency of electrons will increase, the internal resistance of the battery will increase, and the rate performance of the battery will be further affected.

[0079] In some embodiments, the base film includes at least one of a polypropylene film or a polyethylene film. As an example, the base film can be a polypropylene film, a polyethylene film, or a composite film composed of polyethylene and polypropylene.

[0080] In some embodiments, the tensile strength of the diaphragm is 1.139 MPa to 2.186 MPa. As an example, the tensile strength of the diaphragm can be 1.139 MPa, 1.339 MPa, 1.5 MPa, 1.75 MPa, 1.88 MPa, 1.9 MPa, 1.99 MPa, 2.186 MPa, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0081] In some embodiments, the elongation at break of the diaphragm is 14.6% to 45.1%. As an example, the elongation at break of the diaphragm may be 14.6%, 15%, 16.6%, 20%, 26%, 36%, 40%, 45.1%, etc., and of course, it may be other values ​​within the above range, which is not limited here.

[0082] In some embodiments, the contact angle of the diaphragm is 16.274° to 26.458°. As an example, the contact angle of the diaphragm can be 16.274°, 16.585°, 17.696°, 18.189°, 19.264°, 20.368°, 22.357°, 24.563°, 25.987°, 26.458°, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0083] From the data of tensile strength, elongation at break and contact angle of the above-mentioned diaphragm, it can be known that the diaphragm has good mechanical properties and wettability. This is due to the fact that bacitracin or bacitracin metal chelate can provide excellent fiber structure for the diaphragm coating, enhancing the mechanical properties of the diaphragm; and bacitracin or bacitracin metal chelate itself also has many polar functional groups such as -NH2, -COOH and -CONH-, etc., which enhance the wettability of the diaphragm.

[0084] Thus, based on the above scheme, a diaphragm is provided. By setting a coating on the surface of at least one side of the base film along the thickness direction, the existing diaphragm coating has problems such as insufficient mechanical properties and poor interface stability. The diaphragm coating includes composite fibers; the composite fibers include a compound after dehydration condensation of reactants A and reactants B; after reactants A and reactants B are mixed, they can be stably combined in the form of covalent bonds, and are set at the interface of the base film to form a uniform and dense coating. Among them, reactant A includes bacitracin or bacitracin metal chelate, bacitracin can contribute excellent fiber structure to the coating, and it itself also has rich polar groups (-NH2, -COOH or -CONH-, etc.), which makes the composite fiber have excellent softness, high tensile strength, good hydrophilicity and sustained release properties, and enhances its compatibility with the base film. In addition, the short chain of bacitracin has abundant polar functional groups, which can attract lithium ions migrating in the electrolyte and have strong lithium ion transport ability. The bacitracin metal chelate introduces metal into the polypeptide system of bacitracin, which can optimize the metal transport capacity of bacitracin, produce a synergistic effect with the polar functional groups on bacitracin, and further improve the transfer rate of lithium ions of the diaphragm. Reactant B includes hydroxyl-containing polymers, carboxyl-containing polymers, amide-containing polymers or amine-containing polymers. While solving the problem that bacitracin or bacitracin metal chelates are difficult to form a uniform coating on the base film, it can also further enhance the mechanical properties and wettability of the diaphragm. In addition, the coating formed by the reactants obtained by dehydration condensation of reactants A and reactants B also has high temperature stability. Therefore, the coating in the diaphragm of the present invention has higher compatibility with the base film, and also has better mechanical properties. At the same time, it can also improve the cycle life and capacity retention rate of the battery at a higher operating temperature (60°C), and can improve the interface stability and conductivity during the battery cycle.

[0085] Based on the same inventive concept, the present application also provides a method for preparing a diaphragm, the method comprising:

[0086] Adding reactant A to the solution and mixing to obtain a spinning solution, wherein the solution includes reactant B;

[0087] The spinning solution forms a coating on the base membrane by electrostatic spinning to obtain a diaphragm;

[0088] Wherein, the spinning solution contains a compound obtained by dehydration condensation of reactant A and reactant B;

[0089] The reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer.

[0090] In this application, reactant B is used to improve the spinning performance of reactant A, reactants A and reactant B are first prepared into spinning solutions, and a coating is formed on both sides of the base film by electrostatic spinning, and the excellent performance of reactants A and reactant B is comprehensively utilized to finally prepare a diaphragm with excellent performance. The prepared diaphragm coating structure has the characteristics of being dense, uniform and stable. After forming a coating on the surface of the base film in the form of electrostatic spinning, the diaphragm as a whole also has better mechanical properties, and has a significant improvement effect on the high temperature performance and electrical performance of the battery. In addition, the method provided in this application has low preparation cost and simple process, and can be used on a large scale.

[0091] It should be understood that all the features and advantages described above for the "diaphragm" are also applicable to the "method for preparing the diaphragm", and will not be described in detail here.

[0092] In some specific embodiments, the method for preparing the diaphragm specifically comprises the following steps (a) to (c):

[0093] (a) Preparation of spinning solution

[0094] In step (a), preparing the spinning solution includes: preparing a solution of reactant B, adding an appropriate amount of reactant A to the solution containing reactant B, and stirring at room temperature until the reactant A is completely dissolved to obtain the spinning solution.

[0095] In some embodiments, preparing a solution of reactant B includes dissolving reactant B in an aqueous solution, wherein the aqueous solution includes an acid.

[0096] In some embodiments, the mass fraction of the acid in the solution is 55% to 65%. As an example, the mass fraction of the acid in the solution can be 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0097] In some embodiments, the acid includes at least one of formic acid, acetic acid, hydrochloric acid or sulfuric acid. As an example, the acid can be formic acid, acetic acid, hydrochloric acid, sulfuric acid, or a mixture of formic acid and acetic acid.

[0098] In some embodiments, based on the mass of the solution, the mass fraction of reactant B is 1% to 3%. As an example, the mass fraction of reactant B can be 1%, 1.3%, 1.5%, 1.8%, 2%, 2.5%, 2.6%, 2.8%, 3%, etc., and of course it can also be other values ​​within the above range, which are not limited here. The mass fraction of reactant B lower than 1% will cause the viscosity of the electrospinning solution to become low, making it difficult for the fiber to be formed, and the fiber diameter of the spinning product is also uneven, and because reactant B can enhance the strength of the fiber, too low a concentration of reactant B will cause the strength of the spinning fiber to decrease. The mass fraction of reactant B higher than 3% will increase the fiber diameter: too high a concentration of reactant B will cause a significant increase in the viscosity of the solution. In the electrospinning process, the viscosity of the solution has a great influence on the fiber diameter. When the viscosity is high, the tensile resistance of the jet under the action of the electric field increases, and the jet cannot be fully stretched, thereby making the formed fiber diameter thicker. Further, too high a concentration of reactant B will make the molecular chains in the solution more entangled with each other. During the spinning process, these entangled molecular chains may not be evenly distributed inside the fiber, and some molecular chains will gather on the fiber surface, causing the fiber surface to become rough. Moreover, due to the excessive entanglement of molecular chains, the incompletely dissolved reactant A particles may be wrapped on the fiber surface or inside, further affecting the smoothness of the fiber. In addition, too high a concentration of reactant B will also make the fluidity of the solution worse. After the electrospinning is completed, due to the high viscosity between the fibers, the fibers may stick to each other and agglomerate together. This is because the high concentration of reactant B makes the fiber surface carry more sticky components. When the fibers contact each other, they are easy to stick together to form clumps instead of well-dispersed single fibers, which affects the operability and application performance of the fibers.

[0099] In some embodiments, based on the mass of the solution, the mass fraction of reactant A is 20% to 25%. As an example, the mass fraction of reactant A can be 20%, 21%, 22%, 23%, 24%, 25%, etc., and of course it can also be other values ​​within the above range, which are not limited here. The mass fraction of reactant A below 20% will result in limited lithium ion transport capacity, and the resulting diaphragm will be difficult to improve the electrical performance of the battery; if the mass fraction of reactant A is higher than 25%, it will exceed its solubility in the reactant B solution. This will cause part of the reactant A to be unable to completely dissolve, forming aggregates or crystals in the solution. During the electrospinning process, these aggregates or crystals will interfere with the normal formation and stretching of the solution jet. For example, when an electric field is applied to the solution at the nozzle, the aggregated reactant A particles may hinder the continuous outflow of the solution, making it impossible to stably form the jet, resulting in difficulty in forming the fiber, and even nozzle clogging. High concentrations of reactant A will change the physical properties of the solution, and the excessive presence of reactant A will change the density, viscosity and other properties of the solution. In the electrospinning process, the uneven solution properties can cause uneven fiber stretching. When the jet is stretched in the electric field, the stretching degree of the area containing more bacitracin zinc and the area containing less bacitracin zinc is different, and the final fiber diameter will be greatly different, with thicker fibers in some places and thinner fibers in some places, resulting in uneven fiber diameter. High concentration of reactant A will increase the roughness of the fiber surface, and the incompletely dissolved reactant A particles may adhere to the fiber surface, or in the fiber formation process, the uneven distribution of reactant A causes protrusions or depressions in local areas. Finally, the excessive concentration of reactant A will also make the internal structure of the fiber loose, and due to the large presence of reactant A, the orderly arrangement between the molecular chains of reactant B inside the fiber may be destroyed, and the interaction force between the molecular chains is weakened. When stretched by external force, the fiber is easy to break, and its mechanical performance indicators such as tensile strength and elastic modulus will decrease. In some embodiments, the stirring time is 2~3h. As an example, the stirring time can be 2h, 2.5h, 3h, etc., and of course it can also be other values ​​within the above range, which are not limited here.

[0100] (b) Electrospinning

[0101] In step (b), spinning is performed using an electrospinning machine at room temperature. The spinning solution is sucked into a disposable syringe, a precision steel needle is used as a spinneret, the positive high voltage and negative high voltage of the electrospinning equipment are set, a base film is placed on a rotating drum, the relative distance between the spinneret and the rotating drum and the spinning flow rate are controlled, and the spinning is evenly translated left and right so that the spinning is evenly formed on the base film, thus completing the electrospinning step.

[0102] It should be noted that the equipment used for electrospinning is conventional electrospinning equipment, and there are no specific requirements. It only needs to be able to complete the electrospinning steps.

[0103] In some embodiments, the inner diameter of the spinneret is 0.5-0.7 mm. As an example, the inner diameter of the spinneret can be 0.5 mm, 0.6 mm, 0.7 mm, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0104] In some embodiments, the positive high voltage of the electrospinning device spinneret is 15-25KV. As an example, the positive high voltage of the electrospinning device spinneret can be 15KV, 16KV, 17KV, 18KV, 19KV, 20KV, 21KV, 22KV, 23KV, 24KV, 25KV, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0105] In some embodiments, the negative high voltage at the drum of the electrospinning device is -3.5~-2.5KV. As an example, the negative high voltage at the drum of the electrospinning device can be -3.5KV, -3.4KV, -3.3KV, -3.2KV, -3.1KV, -3KV, -2.9KV, -2.8KV, -2.7KV, -2.6KV, -2.5KV, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0106] In some embodiments, the spinning flow rate is 0.6-0.8 mL / h. As an example, the spinning flow rate can be 0.6 mL / h, 0.7 mL / h, 0.8 mL / h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0107] In some embodiments, the distance between the spinneret and the drum is 8 to 15 cm. As an example, the distance between the spinneret and the drum can be 8 cm, 9 cm, 10 cm, 11 cm, 12 cm, 13 cm, 14 cm, 15 cm, etc., and of course, it can be other values ​​within the above range, which is not limited here.

[0108] (c) Drying

[0109] In step (c), the base membrane after electrospinning is transferred to a vacuum oven and dried to obtain a separator.

[0110] In some embodiments, the drying temperature is 35-45° C. As an example, the drying temperature may be 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C., 42° C., 43° C., 44° C., 45° C., etc., and may also be other values ​​within the above range, which are not limited here.

[0111] In some embodiments, the preparation method of Bacitracin metal chelate comprises:

[0112] The bacitracin is dissolved in a solvent and then mixed with a metal salt, and then dialyzed, centrifuged and dried to obtain a bacitracin metal chelate.

[0113] As an example, the preparation method of Bacitracin metal chelate specifically comprises the following steps:

[0114] (1) Weigh a certain amount of bacitracin (BAC) into a beaker, add it to the solvent, and stir at room temperature until it is completely dissolved; then add a certain amount of metal salt, add alkali to adjust the pH value of the solution to neutral or weak alkaline, and then continue stirring for a certain period of time;

[0115] (2) The solution obtained in step (1) is completely sucked into a dialysis bag, which is clamped with a special dialysis bag clamp, placed in deionized water, and rotated at a constant speed by a magnetic stirrer at room temperature to remove excess metal salts;

[0116] (3) pouring the solution obtained in step (2) into a centrifuge tube, centrifuging using a centrifuge, and then discarding the supernatant to obtain a bacitracin metal chelate solution;

[0117] (4) Place the solution obtained in step (3) into a forced air oven, set the temperature, dry it, and then grind it to obtain BACZ powder.

[0118] In some embodiments, the mass volume ratio of bacitracin, metal salt and solvent is (5-30 mg): (15-90 mg): (50-100 mL). As an example, the mass volume ratio of bacitracin, metal salt and solvent can be 5 mg: 15 mg: 50 mL, 9 mg: 35 mg: 60 mL, 15 mg: 50 mg: 80 mL, 20 mg: 80 mg: 90 mL, 25 mg: 45 mg: 70 mL, 28 mg: 88 mg: 98 mL, 30 mg: 90 mg: 100 mL, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0119] In some embodiments, the solvent includes, but is not limited to, at least one of water, ethanol, methanol, or dimethyl sulfoxide. As an example, the solvent can be water, ethanol, methanol, dimethyl sulfoxide, or a mixture of methanol and ethanol.

[0120] In some embodiments, the metal salt includes, but is not limited to, at least one of a metal hydrochloride or a metal sulfate. As an example, the metal salt can be a metal hydrochloride or a metal sulfate.

[0121] In some embodiments, the metal in the metal salt includes, but is not limited to, at least one of zinc, copper, manganese, or nickel. As an example, the metal in the metal salt can be zinc, copper, manganese, or nickel, preferably zinc.

[0122] In some embodiments, in the dialysis step, the specification of the dialysis bag is 800-1200 D. As an example, the specification of the dialysis bag can be 800 D, 900 D, 1000 D, 1100 D, 1200 D, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0123] In some embodiments, in the dialysis step, the water change interval is 3 to 5 hours. As an example, the water change interval can be 3 hours, 4 hours, 5 hours, etc., and of course it can be other values ​​within the above range, which is not limited here.

[0124] In some embodiments, in the dialysis step, the dialysis time is 22 to 26 hours. As an example, the dialysis time can be 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0125] In some embodiments, in the centrifugation step, the centrifugal speed is 8000-10000 rpm. As an example, the centrifugal speed can be 8000 rpm, 9000 rpm, 10000 rpm, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0126] In some embodiments, in the centrifugation step, the centrifugation time is 4 to 6 minutes. As an example, the centrifugation time can be 4 minutes, 5 minutes, 6 minutes, etc., and of course it can be other values ​​within the above range, which is not limited here.

[0127] In some embodiments, in the drying step, the drying temperature is 40-50° C. As an example, the drying temperature may be 40° C., 42° C., 43° C., 44° C., 46° C., 48° C., 49° C., 50° C., etc., and may also be other values ​​within the above range, which are not limited here.

[0128] The bacitracin metal chelate prepared by the above method can be mixed with a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer to prepare a diaphragm coating. In particular, the bacitracin zinc prepared by the above preparation method has a microporous morphology, while the bacitracin zinc purchased on the conventional market does not have a porous morphology.

[0129] Thus, based on the above, after the present invention mixes reactant A and reactant B to prepare a spinning solution, a stable combination can be achieved in the form of a covalent bond, and a uniform and dense coating is formed on the interface of the basement membrane by electrostatic spinning. Wherein, reactant A includes bacitracin or bacitracin metal chelate, bacitracin can contribute excellent fiber structure to the coating, and it also has abundant polar groups (-NH2, -COOH or -CONH-, etc.), which makes the composite fiber have excellent softness, high tensile strength, good hydrophilicity and sustained release properties, and enhances its compatibility with the basement membrane. In addition, the short chain of bacitracin has abundant polar functional groups, which can attract lithium ions migrating in the electrolyte and have strong lithium ion transport capacity. Bacitracin metal chelate introduces metal into the polypeptide system of bacitracin, which can optimize the metal transport capacity of bacitracin, produce synergistic effects with the polar functional groups on bacitracin, and further improve the transfer rate of lithium ions of the diaphragm. Reactant B includes hydroxyl-containing polymers, carboxyl-containing polymers, amide-containing polymers or amine-containing polymers, which can further enhance the mechanical properties and wettability of the diaphragm while solving the problem that bacitracin or bacitracin metal chelate is difficult to form a uniform coating on the base film. In addition, the coating formed by the reactants obtained by dehydration condensation of reactants A and reactants B also has high temperature stability. Therefore, the coating in the diaphragm of the present invention has higher compatibility with the base film and has better mechanical properties. At the same time, it can also improve the cycle life and capacity retention rate of the battery at a higher operating temperature (60°C), and can improve the interface stability and conductivity during the battery cycle. In addition, the method provided in the present application has low preparation cost and simple process, and can be used on a large scale.

[0130] Based on the same inventive concept, an embodiment of the present application further provides a battery, comprising a diaphragm, wherein the diaphragm is the aforementioned diaphragm or a diaphragm prepared by the aforementioned preparation method.

[0131] Since the battery includes the diaphragm provided in the embodiment of the present application, it has relatively excellent thermal stability and mechanical properties, and has a lower battery charge and discharge internal resistance and good high-temperature cycle stability.

[0132] In some embodiments, the battery may be a lithium-ion battery. The battery stacking type may be, for example, a wound or laminated battery, and the structural type may be, for example, a square shell (aluminum shell, steel shell, etc.) battery, a soft pack battery, or a cylindrical battery, etc., without specific limitation, and the battery has excellent high temperature performance and electrical performance.

[0133] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a negative electrode sheet, that is, the battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0134] In this embodiment, there is no limitation on the materials and structures of the positive electrode sheet, the positive current collector, the conductive agent, the binder in the positive active material layer, and the like, and any positive electrode sheet structure and composition known in the art that can be used for secondary batteries can be selected.

[0135] In this embodiment, there is no limitation on the materials and structures of the negative electrode sheet, the negative current collector, the conductive agent, the binder in the negative active material layer, and the like, and the positive electrode sheet structure and components known in the art that can be used for secondary batteries can be selected.

[0136] It should also be noted that the battery of the present application is not limited to the specific material or type of the electrolyte, and the components and types that are known in the art and can be used for secondary batteries can be selected as long as the purpose of the present application can be achieved.

[0137] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.

[0138] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0139] Example 1

[0140] 1. Preparation of Bacitracin Zinc

[0141] Weigh 10 mg of bacitracin (BAC) into a beaker, add 50 mL of deionized water to dissolve it, put it on a stirrer and stir at room temperature for 1 hour until BAC is completely dissolved. The concentration of BAC solution is controlled at about 20%. Then weigh 30 mg of zinc sulfate (ZnSO4) and add it to the bacitracin solution. Use 1 mol / L sodium hydroxide to adjust the pH value of the solution to 7, and then use a stirrer to stir at 40°C for 1 hour. Add zinc sulfate (ZnSO4) to the bacitracin solution and stir it at room temperature for 1 hour using a stirrer. The mass ratio of BAC and ZnSO4 is 1:3.

[0142] Use a rubber-tipped dropper to suck the evenly stirred mixed solution into a dialysis bag of specification 1000D, then place the clamped dialysis bag in a beaker filled with 500mL of deionized water, and use a magnetic stirrer to slowly rotate the dialysis bag at room temperature to allow residual ZnSO4 to pass through the dialysis bag. Change the deionized water every 4 hours, dialyze for 24 hours, and transfer the stirred mixed solution to a 50mL centrifuge tube.

[0143] Place the centrifuge tube containing the mixed solution into a centrifuge, centrifuge at 9000 rpm for 5 minutes, pour out the supernatant and place in a forced air drying oven at 45°C until it is dried and ground into bacitracin zinc (BACZ) powder.

[0144] 2. Preparation of diaphragm

[0145] 10 mg of polyethylene glycol (PEG) was weighed and put into a beaker, and an aqueous solution was added, wherein the aqueous solution contained formic acid, and the mass fraction of formic acid in the aqueous solution was 60%, and a PEG solution with a mass fraction of 1% (based on the mass of the formic acid aqueous solution) was prepared. Then, BACZ powder was added to the PEG solution and stirred evenly using a blender to prepare a 20% mass fraction BACZ / PEG mixed solution (based on the mass of the formic acid aqueous solution). After completion, it was placed at room temperature for 8 hours as a spinning solution; the prepared spinning solution was sucked into the tube with a 10 mL syringe, and a precision steel needle was used as a spinneret with an inner diameter of 0.6 mm, the spinneret and the rotating drum were controlled at 12 cm relative to each other, the spinning flow rate was 0.75 mL / h, the positive high voltage at the needle of the electrospinning instrument was 25 KV, and the negative high voltage at the drum was -3 KV. A base film PP (thickness 10 μm) was placed on the rotating drum, and the needle was evenly translated left and right. The spinning time was 5 hours, and the spinning thickness was controlled at 30 μm.

[0146] Example 2

[0147] The difference between Example 2 and Example 1 is that the amount of zinc sulfate used in Example 2 is 20 mg, and the rest is the same as Example 1.

[0148] Example 3

[0149] The difference between Example 3 and Example 1 is that the amount of zinc sulfate used in Example 3 is 40 mg, and the rest is the same as Example 1.

[0150] Example 4

[0151] The only difference between Example 4 and Example 1 is that the mass fraction of BACZ in the BACZ / PEG mixed solution in Example 4 is 25% (based on the mass of the formic acid aqueous solution), and the rest is the same as Example 1.

[0152] Example 5

[0153] The only difference between Example 5 and Example 1 is that the mass fraction of BACZ in the BACZ / PEG mixed solution in Example 5 is 10% (based on the mass of the formic acid aqueous solution), and the rest is the same as Example 1.

[0154] Example 6

[0155] The only difference between Example 6 and Example 1 is that polyethylene glycol is replaced by polylactic acid in Example 6, and the rest is the same as Example 1.

[0156] Example 7

[0157] The only difference between Example 7 and Example 1 is that polyethylene glycol is replaced by polyamide in Example 7, and the rest is the same as Example 1.

[0158] Example 8

[0159] Weigh 10 mg of polyethylene glycol (PEG) and put it into a beaker, add an aqueous solution, wherein the aqueous solution contains formic acid, and the mass fraction of formic acid in the aqueous solution is 60%, to prepare a PEG solution with a mass fraction of 1% (based on the mass of the formic acid aqueous solution), then add BAC powder to the PEG solution and stir it evenly with a stirrer to prepare a 20% mass fraction BAC / PEG mixed solution (based on the mass of the formic acid aqueous solution), and then leave it at room temperature for 8 hours as a spinning solution;

[0160] The prepared spinning solution was sucked into the tube with a 10mL syringe. The precision steel needle used as the spinneret had an inner diameter of 0.6mm, the spinneret and the rotating drum were controlled at 12cm relative to each other, the spinning flow rate was 0.75mL / h, the positive high voltage at the needle of the electrospinning instrument was 25KV, the negative high voltage at the drum was -3KV, a base film PP (thickness 10μm) was placed on the rotating drum, the needle was evenly translated left and right, the spinning time was 5h, and the spinning thickness was controlled at 30μm.

[0161] Example 9

[0162] The difference between Example 9 and Example 1 is that zinc sulfate is replaced by copper sulfate in Example 9, and the rest is the same as Example 1.

[0163] Example 10

[0164] The only difference between Example 10 and Example 1 is that zinc sulfate is replaced by nickel sulfate in Example 10, and the rest is the same as Example 1.

[0165] Embodiment 11

[0166] 1. Preparation of Bacitracin Zinc

[0167] Weigh 10 mg of bacitracin (BAC) in a beaker, add 50 mL of deionized water to dissolve it, put it on a stirrer and stir at room temperature for 1 hour until BAC is completely dissolved. The concentration of BAC solution is controlled at about 20%. Then weigh 30 mg of zinc sulfate (ZnSO4) and add it to the bacitracin solution. Use 1 mol / L sodium hydroxide to adjust the pH value of the solution to 8. Then use a stirrer to stir at 40 ° C for 1 hour. The mass ratio of BAC and ZnSO4 is 1:2;

[0168] Use a rubber-tipped dropper to suck the mixed solution into a dialysis bag of specification 800D, then place the clamped dialysis bag in a beaker filled with 500mL deionized water, and use a magnetic stirrer to slowly rotate the dialysis bag at room temperature to allow residual ZnSO4 to pass through the dialysis bag. Change the deionized water every 5 hours, dialyze for 25 hours, and transfer the stirred mixed solution to a 50mL centrifuge tube;

[0169] Place the centrifuge tube containing the mixed solution in a centrifuge, centrifuge at 10,000 rpm for 5 minutes, pour out the supernatant and place in a forced air drying oven at 40°C until it is dried and ground into bacitracin zinc (BACZ) powder;

[0170] 2. Preparation of diaphragm

[0171] Weigh 20 mg of polyethylene glycol (PEG) and put it into a beaker, add an aqueous solution, wherein the aqueous solution contains formic acid, the mass fraction of formic acid in the aqueous solution is 60%, and prepare a PEG solution with a mass fraction of 2% (based on the mass of the formic acid aqueous solution), then add BACZ powder into the PEG solution and stir it evenly with a stirrer to prepare a 25% mass fraction BACZ / PEG mixed solution (based on the mass of the formic acid aqueous solution), and then leave it at room temperature for 8 hours as a spinning solution;

[0172] The prepared spinning solution was sucked into the tube with a 10mL syringe. The precision steel needle used as the spinneret had an inner diameter of 0.6mm, the spinneret and the rotating drum were controlled at 12cm relative to each other, the spinning flow rate was 0.75mL / h, the positive high voltage at the needle of the electrospinning instrument was 20KV, the negative high voltage at the drum was -3KV, a base film PP (thickness 15μm) was placed on the rotating drum, the needle was evenly translated left and right, the spinning time was 5h, and the spinning thickness was controlled at 20μm.

[0173] Example 12

[0174] The only difference between Example 12 and Example 1 is that the spinning thickness of Example 12 is 25 μm, and the rest is the same as Example 1.

[0175] Example 13

[0176] The only difference between Example 13 and Example 1 is that the spinning thickness of Example 13 is 15 μm, and the rest is the same as Example 1.

[0177] Comparative Example 1

[0178] The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 directly uses the PP base film as the battery separator, and the rest is the same as Example 1.

[0179] Comparative Example 2

[0180] The difference between Comparative Example 2 and Example 1 is that the spinning solution of Comparative Example 2 does not contain bacitracin zinc, and the rest is the same as Example 1.

[0181] Comparative Example 3

[0182] The difference between Comparative Example 3 and Example 1 is that the spinning solution of Comparative Example 3 does not contain polyethylene glycol, and the rest is the same as Example 1.

[0183] Since bacitracin zinc could not form a coating on the base film, the composite membrane could not be obtained in Comparative Example 3.

[0184] Performance Testing

[0185] 1. Performance test of composite diaphragm:

[0186] (1) Tensile strength test: Clamp the diaphragms of each embodiment and comparative example symmetrically between the upper and lower clamps, and the distance from the clamping point to the overlapped end is usually (50±1) mm. Ensure that the clamp can stably fix the sample to avoid sliding or falling off during the test. Start the test instrument and apply external force to the sample at a steady speed of (5±1) mm / min until the sample breaks, and record the tensile strength.

[0187] (2) Elongation at break test: Clamp the diaphragms of each embodiment and comparative example symmetrically between the upper and lower clamps, with the distance from the clamping point to the overlapped end being generally (50±1) mm. Ensure that the clamps can stably fix the specimen to avoid slipping or falling off during the test. Start the test instrument and apply an external force to the specimen at a steady speed of (5±1) mm / min until the specimen breaks, and record the elongation at break.

[0188] (3) Contact angle test: Place the cut membranes of each embodiment and comparative example on a glass slide to ensure that the glass slide and the membrane are level. Use the contact angle tester syringe to draw a suitable amount of electrolyte and slowly drop it on the membrane. The contact angle tester acquisition system will automatically record the contact between the droplet profile and the membrane, and then process the recorded data.

[0189] The test results of the diaphragms of various embodiments and comparative examples are shown in Table 1.

[0190] 2.Battery performance test:

[0191] Preparation of lithium-ion batteries

[0192] S1 cathode sheet preparation

[0193] Lithium titanate, a conductive agent and a binder are mixed and stirred in a mass ratio of 8:1:1, and then (N-methyl-2-pyrrolidone) NMP solvent is added and mixed evenly to prepare a positive electrode slurry, and the positive electrode slurry is evenly coated on an aluminum foil coated with a conductive carbon layer in a certain proportion, and vacuum dried at 80-120°C to obtain a positive electrode material coated with an active material layer. The positive electrode material is passed through a tablet press to obtain a positive electrode sheet.

[0194] Among them, the binder is polyvinylidene fluoride (PVDF); the conductive agent can be one or more of SP, CNT, and graphite. SP is selected for this test.

[0195] S2 battery preparation

[0196] The positive electrode sheet / copper foil, separator, and negative electrode sheet are assembled together to form a battery, wherein the separator must be able to completely wrap the positive and negative electrode sheets, and the electrolyte is injected into the battery to finally form a Li-Cu half-cell or lithium titanate battery.

[0197] The positive electrode is made of commercially available copper foil after being pressed by a sheet press. The negative electrode is made of lithium metal sheet. The electrolyte uses lithium salt bis(trifluoromethylsulfonyl)imide lithium, and the lithium salt concentration is 1.0 mol -1 , the solvent is 1,3-dioxolane and ethylene glycol dimethyl ether.

[0198] Conduct electrochemical performance tests on batteries

[0199] (1) Cycle performance test: At 25°C, charge the battery to 2.5V at 2C constant current and constant voltage, with a cut-off current of 0.05C; let it stand for 60 min, then discharge it to 1.5V at 2C. Continue the above process until the capacity decays to 80% of the initial capacity, and record the number of cycles.

[0200] (2) Capacity retention rate test: At 25°C, charge the battery to 2.5V at 2C constant current and constant voltage, with a cut-off current of 0.05C; let it stand for 60 minutes, then discharge it to 1.5V at 2C. Continue the above process and record the number of cycles.

[0201] (3) Initial efficiency test: The test conditions are deposition capacity of 0.5 mAh / cm² and current density of 1 mA / cm². At 25°C, the current density is set to 1 mA / cm², the capacity is set to 0.5 mAh / cm², constant current is charged to the set capacity, left to stand for 60 minutes, and then discharged at 1 mA / cm². The above process is continued and the number of cycles is recorded.

[0202] The test results of each embodiment and comparative example are shown in Table 2.

[0203] (4) Cycle performance test at 60°C: At 60°C, charge the battery to 2.5V at 2C constant current and constant voltage, with a cut-off current of 0.05C; let it stand for 60 min, then discharge it to 1.5V at 2C. Continue the above process until the capacity decays to 80% of the initial capacity, and record the number of cycles.

[0204] (5) Capacity retention rate test at 60°C: At 60°C, charge the battery at 2C constant current and constant voltage to 2.5V, with a cut-off current of 0.05C; let it stand for 60 minutes, then discharge it at 2C to 1.5V. Continue the above process and record the number of cycles.

[0205] The test results of each embodiment and comparative example are shown in Table 3.

[0206]

[0207]

[0208]

[0209] It can be seen from Table 1 that Example 1 has the best tensile strength and wettability compared with other examples and comparative examples, and can effectively improve the mechanical properties and wettability of the diaphragm. The polar functional groups (-NH2, -COOH and -CONH-, etc.) and microchannels on BACZ can guide the uniform embedding and extraction of lithium ions, inhibiting the growth of lithium dendrites.

[0210] It can be seen from Table 2 that when BACZ / PEG is spun as a diaphragm coating, it has the longest cycle life and the highest capacity retention rate compared with other embodiments and comparative examples, which can prove that BACZ / PEG effectively improves the cycle performance of the battery and inhibits the growth of lithium dendrites. At the same time, the improvement in the first efficiency can also indirectly prove that BACZ / PEG with the introduction of metal ions has the best conductivity.

[0211] It can be seen from Table 3 that when BACZ / PEG is spun as a separator coating, it has the longest cycle life and the highest capacity retention rate at an ambient temperature of 60°C. This proves that BACZ / PEG can improve the cycle performance of batteries under high temperature conditions.

[0212] Figure 1 This is a SEM image of bacitracin zinc prepared in Example 1 of the present invention. Figure 1 It can be seen that the prepared bacitracin zinc has a microporous morphology.

[0213] Figure 2 The composite membrane provided in Example 1 of the present invention is assembled into a battery and cycled 100 times at 25°C. The SEM image of bacitracin zinc in the surface coating of the composite membrane is shown in FIG. Figure 2It can be seen that the microporous structure on the surface of bacitracin zinc still exists after 100 cycles, indicating that bacitracin zinc has good cycle stability in the battery.

[0214] Figure 3 The surface SEM image of the spinning coating provided in Example 1 of the present invention is shown. Figure 3 It can be seen that BACZ / PEG can be spun into uniform composite fibers.

[0215] Figure 4 Shown are the EIS graphs of the Li-Cu half-cell during the cycle of Comparative Example 1 and Example 1 of the present invention. It can be seen from the EIS characterization that during the battery cycle, the impedance of Example 1 remains almost unchanged, while the impedance of Comparative Example 1 gradually increases. It can be seen that BACZ / PEG can improve the interface stability and conductivity during the battery cycle.

[0216] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0217] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0218] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0219] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0220] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A diaphragm, characterized in that: The diaphragm comprises: Basement membrane; A coating layer is disposed on at least one side surface of the base film along the thickness direction, and the coating layer includes composite fibers; The composite fiber includes a compound obtained by dehydration condensation of reactant A and reactant B; Wherein, the reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer.

2. The diaphragm according to claim 1, characterized in that The mass ratio of the reactant A to the reactant B is (20-25): (1-3); and / or, the bacitracin metal chelate comprises at least one of bacitracin zinc, bacitracin copper, bacitracin manganese or bacitracin nickel; And / or, the reactant B includes at least one of polyethylene glycol, polylactic acid, polyamide, cellulose acetate or polyvinyl alcohol.

3. The diaphragm according to claim 1, characterized in that The thickness of the coating is 10 μm to 35 μm; And / or, the base film has a thickness of 10 μm to 20 μm; and / or, the thickness ratio of the coating layer to the base film is 0.5 to 3.5; And / or, the base film includes at least one of a polypropylene film or a polyethylene film.

4. The diaphragm according to any one of claims 1 to 3, characterized in that: The tensile strength of the diaphragm is 1.139Mpa ~ 2.186Mpa; And / or, the elongation at break of the diaphragm is 14.6% to 45.1%; And / or, the contact angle of the diaphragm is 16.274°~26.458°.

5. A method for preparing a diaphragm, characterized in that: The following steps are involved: Adding reactant A to the solution and mixing to obtain a spinning solution, wherein the solution includes reactant B; The spinning solution forms a coating on the base membrane by electrostatic spinning to obtain a diaphragm; Wherein, the spinning solution contains a compound obtained by dehydration condensation of reactant A and reactant B; The reactant A comprises at least one of bacitracin or bacitracin metal chelate, and the reactant B comprises at least one of a hydroxyl-containing polymer, a carboxyl-containing polymer, an amide-containing polymer or an amine-containing polymer.

6. The method for preparing a diaphragm according to claim 5, characterized in that: The electrospinning step satisfies at least one of the following characteristics (1) to (4): (1) The inner diameter of the spinneret is 0.5~0.7mm; (2) The distance between the spinneret and the roller is 8~15cm; (3) The spinning flow rate is 0.6~0.8mL / h; (4) The positive high voltage of the electrospinning equipment spinneret is 15~25KV, and the negative high voltage at the roller is -3.5~-2.5KV.

7. The method for preparing a diaphragm according to claim 5, characterized in that: The solution is an aqueous solution, the aqueous solution includes an acid, and the solution satisfies at least one of the following characteristics (1) to (4): (1) The mass fraction of the acid in the solution is 55% to 65%; (2) The acid includes at least one of formic acid, acetic acid, hydrochloric acid or sulfuric acid; (3) Based on the mass of the solution, the mass fraction of the reactant B is 1% to 3%; (4) Based on the mass of the solution, the mass fraction of the reactant A is 20% to 25%.

8. The method for preparing a diaphragm according to claim 5, characterized in that: The preparation method of the Bacitracin metal chelate comprises: The bacitracin is dissolved in a solvent and then mixed with a metal salt, and then dialyzed, centrifuged and dried to obtain a bacitracin metal chelate.

9. The method for preparing a diaphragm according to claim 8, characterized in that: The method for preparing the Bacitracin metal chelate satisfies at least one of the following characteristics (1) to (7): (1) The mass volume ratio of the bacitracin, the metal salt and the solvent is (5-30 mg): (15-90 mg): (50-100 mL); (2) The solvent includes at least one of water, ethanol, methanol or dimethyl sulfoxide; (3) The metal salt comprises at least one of a metal hydrochloride or a metal sulfate, and the metal in the metal salt comprises at least one of zinc, copper, manganese or nickel; (5) In the dialysis step, the specification of the dialysis bag is 800~1200D, the water change interval is 3~5h, and the dialysis time is 22~26h; (6) In the centrifugation step, the centrifugal speed is 8000-10000 rpm and the centrifugal time is 4-6 min; (7) In the drying step, the drying temperature is 40-50°C.

10. A battery comprising a separator, characterized in that: The diaphragm is the diaphragm according to any one of claims 1 to 4 or the diaphragm prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Diaphragm, preparation method thereof, secondary battery and electric equipment

    CN113594631A

  • Electrospinning-based aqueous zinc ion battery diaphragm and preparation method thereof

    CN118292277A